Oral Health Status of the Professional Soccer Players in Thailand - Chantaramanee, Ariya (UI Scholars Hub, 2016)
Objectives: To evaluate the oral health status of the professional soccer players in Thailand. Methods: Twenty-five Thailand professional soccer players’ oral conditions were examined and included in this study. DMFT, Quigley & Hein plaque index (PI), Löe & Silness gingival index, World Health Organization malocclusion index, pocket depth, TMJ examination and history of dental trauma were recorded. Results: The results demonstrated poor oral health level including dental caries (84%), DMFT score mean was 10.08, dental attrition (60%) and periodontal pocket (36%). Thirty percent of all players presented bruxism. More than 40% of athletes were bothered by their oral health with 28% reporting an impact on quality of life and 18% on training and performance. Conclusion: The oral health of Thai professional soccer players was poor that may result in negative impact on well-being, training and performance. As oral health is an important element of overall health and well-being, health promotion is required to optimize soccer player performance.